2021
DOI: 10.1016/j.clinimag.2020.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT findings of coronavirus disease 2019 (COVID-19): A comprehensive meta-analysis of 9907 confirmed patients

Abstract: We performed a systematic review and meta-analysis of the prevalence of chest CT findings in patients with confirmed COVID-19 infection. Methods: Systematic review of the literature was performed using PubMed, Scopus, Embase, and Google Scholar to retrieve original studies on chest CT findings of patients with confirmed COVID-19, available up to 10 May 2020. Data on frequency and distribution of chest CT findings were extracted from eligible studies, pooled and meta-analyzed using random-effects model to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 121 publications
3
29
0
Order By: Relevance
“…2,3 Pleural thickening, nodules, pleural effusion, lymphadenopathy, cavitation and pneumothorax were identified as atypical findings of COVID-19 pneumonia. 1 Recently, we observed an increase in the incidence of cavitary lung lesions during COVID-19 pandemia in our hospital which operates as a pandemic hospital in the region. Cavitary lung lesions detected in COVID-19 cases have started to emerge as only a few case reports in the literature.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…2,3 Pleural thickening, nodules, pleural effusion, lymphadenopathy, cavitation and pneumothorax were identified as atypical findings of COVID-19 pneumonia. 1 Recently, we observed an increase in the incidence of cavitary lung lesions during COVID-19 pandemia in our hospital which operates as a pandemic hospital in the region. Cavitary lung lesions detected in COVID-19 cases have started to emerge as only a few case reports in the literature.…”
mentioning
confidence: 78%
“… 2 , 3 Pleural thickening, nodules, pleural effusion, lymphadenopathy, cavitation and pneumothorax were identified as atypical findings of COVID-19 pneumonia. 1 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common classical finding in thoracic CT of SARS-CoV-2 infected patients was Ground Glass Opacities [55]. Meta-analysis conducted by Zarifian A. et al [56] In our review, the overall incidence of crazy cave pattern is observed in 24.47 % COVID-19 patients, while the recent meta-analysis conducted by Bao C. et al [57], Zheng Y. et al [58] and Zhu J. et al [59] and Zhou X. et al [70] showed pooled percentages as 14.81 %, 24 %, [42] 305 35.6 % and 20 % respectively. Sub-pleural bands is another typical radiological feature in SARS-CoV-2 infections, and was observed as 55.61 %, in our review while the meta-analysis conducted by Zheng Y. et al 58 % of the patients developed sub-pleural bands during coronavirus disease [58].…”
Section: Discussionmentioning
confidence: 99%
“…Computerized tomography (CT) has also become a major diagnostic and assessment tool, and it is now considered as a practical and reliable method in COVID-19 patients [ 22 , 23 ]. Typical radiologic findings include chest CT anomalies [ 24 , 25 ] (e.g., multifocal groundglass opacities with or without consolidation in lung regions close to visceral pleural surfaces, crazy paving, patterns compatible with organizing pneumonia, and thickened vessels with parenchymal abnormalities). Patients are assessed using the 1-5 scale COVID-19 Reporting and Data System (CO-RADS) to determine the likelihood of infection, with CO-RADS 4 and 5 considered to be diagnostic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%